KEPEDULIAN DAN KEBERSIHAN LINGKUNGAN SISWA-SISWI SDN 3 SAWOJAJAR KOTA MALANG - Siti Nur Qumariyah; Abdul Hamid Muhadjir; Toni Budiarsono; Susandi Susandi; Artifa Soraya; Tria Muhammad Aris (JPM PAMBUDI, 2023)
A clean environment is everyone’s dream. However, creating an environment that is uncluttered and eye-chatching is a challenge in itself. We often ignore environmental hygiene issues in our immediate environment, especially the school environment, due to busyness and other factors. A clean environment has many advantages for everyone. The aim is to increase the participation of school members in making the environment around the school clean and unpolluted. The program of activities is carried out in an environmental care model with a community service team consisting of lecturers and students of Ikip Budi Utomo Malang. Their activities through efforts to clean up the school yard at SDN 3 Sawojajar. In general, school members are aware of the importance of maintaining a clean school for environmental preservation and health improvement. However, in terms of increasing this understanding, continuous motivation is needed both from the government and from instutions related to the environment.